Testing the limits of Bioethics: the case of DTC Genetic Testing - Ζέρβα (Sophia Zerva), Σοφία; Λαχανά (Olympiada Lachana), Ολυμπιάδα; Μπουραζάνη (Eleni Mpourazani), Ελένη; Παπουτσάκη (Eleftheria Papoutsaki), Ελευθερία; Πετρόπουλος (Konstantinos Petropoulos), Κωνσταντίνος; Χριστοφίδη (Mairy Christophidi), Μαίρη; Κάτσιλα (Theodora Katsila), Θεοδώρα; Πατρινός (Giorgos Patrinos), Γεώργιος (Bioethica, 2017)
Direct-To-Consumer (DTC) genetic tests are commercial services provided online, in drugstores and/or via television and press devoid of the consultation by a health professional or geneticist. Today, there are issues regarding their data validity and interpretation and the ethics of their use, as they allow access to the users’ genetic makeup. Indeed, DTC genetic services can influence consumers’ private life as well as the lives of those around them. We feel that DTC genetic tests and services need to be regulated and notably, regulation measures should be standardized among national and multinational regulatory bodies.